IDENTIDADE E DIFERENÇA ÉTNICO-RACIAL EM CURRÍCULOS E PROGRAMAS: afirmação ou silenciamento? - Pereira, Suelí Borges (2006)
The treatment given to the ethnic-racial question in the pertaining to school resume of 5ª is approached 8ª series. It has as objective generality to analyze if the pertaining to school resume of 5ª 8ª series is worked in the perspective of affirmation or silenciamento of the identities and ethnic-racial differences of the black segment. For such analysis, the produced bibliographical research is appealed to it on the thematic one and the half interview structuralized carried through with 07 professors of you discipline them of History, Geography and Portuguese Language. It is treated to answer some relative questions to the considered object as the conceptions of the professors concerning the racial relations in Brazil. Quarrels are presented on the identity of the citizen in modernity, evidencing that the educative program of the same one consisted of the idea of universal citizen excluding the different identities. Problematizam the different speeches on related resume and other concepts it. One concludes that the resume of Portuguese Language has not contributed for the affirmation of the identity and difference of the black segment for silencing and/or deturpar definitive contents. This improper treatment also occurs in them disciplines of History and Geography when treating to the question of the traffic, the slavery and the African Continent. Of preponderant form the resume is based on the contributions of the represented européias cultures in didactic books. In face of these conclusions they are suggested didactic-pedagogical actions in the perspective of a multicultural education as alternative for affirmation of the identity and ethnic-racial difference of the black segment